Efektivitas Hukum Pemenuhan Hak Restitusi Terhadap Tindak Pidana Perdagangan Orang di Kota Makassar - Saodana, Shafira; Muchtar, Syamsuddin; Azisa, Nur (Alauddin Law Development Journal (ALDEV), 2023)
This study aims to analyze the effectiveness of the law on the fulfillment of the right of restitution Against Trafficking in Persons in Makassar. This study uses empirical legal methods, using a qualitative approach. The results of this study are (1) the fulfillment of the right of restitution to victims of trafficking in Persons is regulated in Law Number 21 of 2007 concerning the eradication of trafficking in Persons. The public prosecutor informs the victim of the right to request restitution which then the public prosecutor informs the amount of losses suffered by the victim due to the crime of trafficking in persons. (2) the effectiveness of the fulfillment of the right to restitution of victims of trafficking in Persons has not been effective because the law enforcement officers, especially investigators and prosecutors lack understanding related to restitution submission